Does mixing age groups in early childhood education settings support children's language development?. Issue 3 (3rd July 2019) - Justice, Laura M.; Logan, Jessica A.; Purtell, Kelly; Bleses, Dorthe; Højen, Anders
ABSTRACT: As early childhood education programming expands across the globe, there is an increased need to understand how features of these programs influence children's development. The composition of children's age within a classroom is one such feature, although it is much less studied than other features. Theoretical and empirical evidence suggests that children's development may be influenced by the age range of their classmates. This study examines the relations between classroom age variability on children's vocabulary development for 2, 743 children between the ages of two years, nine months, and six years, 11 months enrolled in early childhood education settings in Denmark. Findings indicate a significant nonlinear relationship between the range of child age within a classroom and children's vocabulary development, such that classrooms with a maximum age range of 24 months were associated with the greatest gains in vocabulary growth. Results give direction to policy efforts focused on expansion of early childhood education programming.